Evaluating the impact of lifestyle modifications on hypertensive heart disease - Omar Baoum, Shada; Anbarserri, Faris Mansour; Alhassan, Shahad Emad; Hani, Hassan Fuad Al; Almutairi, Faisal Nashmi; Sulayman, Mohammad Laith; Alfadhli, Jumana Laith; Nass, Omar Adel; Alsehemi, Abdulaziz Omar; Albeetar, Wail Mohammed (International Journal Of Community Medicine And Public Health, 2024)
Hypertensive heart disease (HHD) is a significant cause of cardiovascular morbidity and mortality, resulting from chronic hypertension and leading to complications such as left ventricular hypertrophy, heart failure, and ischemic heart disease. Lifestyle modifications, including dietary changes, physical activity, weight management, stress reduction, and smoking cessation, are essential non-pharmacological interventions that can effectively manage hypertension and prevent the progression to HHD. The DASH diet, reduced sodium intake, regular exercise, and weight loss have been shown to lower blood pressure and improve cardiovascular health. Additionally, stress management techniques like yoga, meditation, and cognitive-behavioral therapy contribute to better BP control. Smoking cessation provides immediate benefits, lowering both blood pressure and cardiovascular risk. This review evaluates the impact of these lifestyle modifications on hypertensive heart disease, highlighting their role in reducing blood pressure, preventing left ventricular hypertrophy, and improving heart function. While pharmacological treatments remain important, lifestyle changes should be prioritized as part of a comprehensive approach to managing hypertension and mitigating cardiovascular risks. Ongoing research is crucial for further understanding the long-term benefits of these interventions in individuals with hypertensive heart disease.